The role of social learning and social support in reducing academic anxiety and enhancing achievement motivation among students - Anggito, Albi; Ismail, Putri Roka; Lubis, Andreas; Marpaung, Claudia (Priviet Social Sciences Journal, 2025)
This study aims to examine the contribution of social learning and social support to reducing academic anxiety and stimulating achievement motivation in Elementary School Teacher Education students. The method used is a quantitative correlational approach involving a total of 150 undergraduate students selected through proportional random sampling. The Likert scale instruments used included social learning, social support, academic anxiety, and student achievement motivation. Data analysis used in this study is multiple regression and mediation with the aim of testing the direct and indirect relationships between variables. The research findings provide information that social learning significantly reduces academic anxiety and increases student achievement motivation. Other findings of the research show that social support has a direct and significant effect on increasing achievement motivation and functions as a partial mediator in the relationship between social learning and achievement motivation. Data analysis of academic anxiety also shows a negative effect on achievement motivation, indicating that academic anxiety becomes a psychological barrier to optimal academic achievement. The results of this study also demonstrate the central role of collaborative learning environments and mutually supportive social interactions in improving the emotional well-being and increasing the motivation of student teachers. The practical implications of this research for higher education institutions highlight the need to strengthen peer learning structures, mentoring systems, and socio-emotional support services. This study also contributes to the relevant literature by integrating social learning theory and social support theory in the context of elementary school teacher education. Furthermore, this study provides comprehensive data to understand how social and psychological factors can work together to shape students' academic motivation.